Assessment of the effect of land use /land cover changes on total runoff from Ofu River catchment in Nigeria - Meshach Ileanwa Alfa; M A Ajibike; Donatus B Adie; O J Mudiare (Brawijaya University, 2018)
The total runoff from a catchment is dependednt on both the soil characteristics and the land use/land cover (LULC) type. This study was conducted to examine the effect of changes in land cover on the total runoff from Ofu River Catchment in Nigeria. Classified Landsat imageries of 1987, 2001 and 2016 in combination with the soil map extracted from the Digital Soil Map of the World was used to estimate the runoff curve number for 1987, 2001 and 2016. The runoff depth for 35 years daily rainfall data was estimated using Natura Resource Conservation Services Curve Number (NRCS-CN) method. The runoff depths obtained for the respective years were subjected to a one-way analysis of variance at 95% level of significance. P-value < 0.05 was taken as statistically significant. Runoff curve numbers obtained for 1987, 2001 and 2016 were 61.83, 63.26 and 62.79 respectively. The effects of the changes in LULC for 1987-2001, 2001-2016 and 1987-2016 were statistically significant (P<0.001) at 95% confident interval. The average change in runoff depths were 79.81%, -11.10% and 48.09% respectively for 1987-2001, 2001-2016 and 1987-2016. The study concluded that the changes in LULC of the catchment had significant effect on the runoff from the catchment.